2017
DOI: 10.1051/0004-6361/201731055
|View full text |Cite
|
Sign up to set email alerts
|

The MUSE-Wide survey: A first catalogue of 831 emission line galaxies

Abstract: We present a first instalment of the MUSE-Wide survey, covering an area of 22.2 arcmin 2 (corresponding to ∼20% of the final survey) in the CANDELS/Deep area of the Chandra Deep Field South. We use the MUSE integral field spectrograph at the ESO VLT to conduct a full-area spectroscopic mapping at a depth of 1 h exposure time per 1 arcmin 2 pointing. We searched for compact emission line objects using our newly developed LSDCat software based on a 3D matched filtering approach, followed by interactive classific… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
75
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 98 publications
(80 citation statements)
references
References 67 publications
(72 reference statements)
5
75
0
Order By: Relevance
“…We collect spectroscopic redshifts for 537 X-ray sources. The spectroscopic redshifts of 468 X-ray sources are from the 7 Ms catalog, and 69 X-ray sources are from 3D-HST survey (Momcheva et al 2016), Inami et al (2017), Herenz et al (2017), and VANDELS 1 (Pentericci et al 2018), respectively. There are still 254 X-ray sources without spectroscopic redshifts.…”
Section: Redshift Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…We collect spectroscopic redshifts for 537 X-ray sources. The spectroscopic redshifts of 468 X-ray sources are from the 7 Ms catalog, and 69 X-ray sources are from 3D-HST survey (Momcheva et al 2016), Inami et al (2017), Herenz et al (2017), and VANDELS 1 (Pentericci et al 2018), respectively. There are still 254 X-ray sources without spectroscopic redshifts.…”
Section: Redshift Selectionmentioning
confidence: 99%
“…Table 1 present the redshift, the class and the origin of the redshift, respectively. "M16", "S16", "H17", "I17", and "P18" represent 3D-HST catalog, ZFOURGE catalog, Inami et al (2017), Herenz et al (2017), and VANDELS catalog, respectively. Columns 2 and 3 of Table 3 are redshift and redshift type of each X-ray source.…”
Section: Redshift Selectionmentioning
confidence: 99%
“…Traditionally, LAEs have been detected using narrow band filters while broad band filters are used to detect LBGs. In addition, multi-object or integral field spectroscopy have been used recently to successfully detect high-z sources (e.g., Herenz et al 2017). Many previous studies have dealt with both types of objects at different redshifts (e.g., Hu et al 1998;Shapley et al 2003;Steidel et al 2003;Malhotra & Rhoads 2004;Steidel et al 2005;Gronwall et al 2007;Iwata et al 2007;Ouchi et al 2008;McLure et al 2009;Oesch et al 2010;Ouchi et al 2010;van der Burg et al 2010;Bouwens et al 2014Bouwens et al , 2015Cassata et al 2015;Sobral et al 2017,b, among others).…”
Section: Introductionmentioning
confidence: 99%
“…Herenz & L. Wisotzki) is given. A link to download the software is provided on the MUSE Science Web Service 9 , and it is also available via the Astrophysics Source Code Library 10 (Herenz & Wistozki 2016). LSDCat is documented in two ways.…”
Section: Discussionmentioning
confidence: 99%
“…These are based on our experience with applying the code on MUSE datacubes, searching for faint emission lines from high-redshift galaxies (first results presented in Bacon et al 2015;and Bina et al 2016; more will be reported in Herenz et al 2017). We intend these guidelines to be instructive for the potential LSDCat user, but they should not be understood as recipes.…”
Section: Guidelines For the Usage Of Lsdcatmentioning
confidence: 99%